Growth response to climatic change over 120 years for Alnus viridis and Salix glauca in West Greenland. (25th September 2014) - Jørgensen, Rasmus H.; Hallinger, Martin; Ahlgrimm, Svenja; Friemel, Juliane; Kollmann, Johannes; Meilby, Henrik; Michalet, Richard
Abstract Questions Which climatic variables are the main determinants of radial growth and to what extent does their effect on growth vary among species? What are the similarities between the temporal radial growth patterns of the two common shrub species, Alnus viridis and Salix glauca? Do changing growth conditions over the past 120 yr and their predicted impact on growth match shrub expansion observed in the region? Location Arsuk Fjord and Disko Bay regions, W Greenland. Methods Alnus viridis and S. glauca specimens were sampled in the field and radial growth was analysed using standard dendrochronological methods ('response functions'). The identified climatic variables were applied to model radial growth using a linear mixed model and predict the growth for 1890–2010. Results The main determinants of radial growth were summer temperatures and, although not significant in the final models, spring precipitation. The empirical chronologies showed only somewhat similar growth patterns. They responded to similar sets of climatic variables, but their similarity was weakened because of the low number of replicates and local differences in growth conditions. The similarity between predicted (modelled) chronologies was higher, which was related to the response to similar sets of climatic variables and high correlation between climatic variables across long distances. Conclusion Overall, estimated growth did not increase over the past 120 yr, but considerable variations in growth are conspicuous and match known historical patterns of the Atlantic Multidecadal Oscillation. Perspectives regarding the observed shrub expansion in W Greenland are discussed, and based on the estimated growth patterns, we consider it unlikely that the recent 10–15‐yr period of favourable climate is the main responsible cause.